(untitled) (Current Horticulture, 2024)
A field experiment was conducted to find out the impact of pre- harvest foliar spray of nutrients and agrochemicals on fruit yield and quality parameters of ber (Zizyphus mauritiana Lamk) during 2022-23 and 2023-24 at SKN College of Agriculture, Jobner, Rajasthan. Among nutrients and agrochemicals, application of T11 (ZnSO4 @ 4g/L + CaCl2 @ 2g/L + chitosan @ 1.5g/L +salicylic acid @ 1g/L) to individual plants was significantly superior to all other treatments, but it was on a par with T9 (CaCl2 @ 2g/L + salicylic acid @ 1g/L), T7 (ZnSo4 @ 4g/L + salicylic acid @ 1g/L) and T5 (ZnSO4 @ 4g/L + CaCl2 @ 2g/L). In treatment T11 (ZnSo4 @ 4g/L + CaCl2 @ 2g/L + chitosan @ 1.5g/L + salicylic acid @ 1g/L), an increase in days taken to first harvesting (137.00 days), days taken to complete harvesting (57.11 days), fruit weight (18.51 g), diameter of fruits (3.59 cm), fruit yield (38.01 kg/tree), fruit yield (105.68 q/ ha), maximum TSS% (19.05 0Brix) and minimum titratable acidity (0.415 %) were recorded.